Effects of Differential Stress and Mental Health on Substance Use among College Students - Avdi Avdija; Arif Akgul (Utan Kayu Publishing, 2026)
Substance use among college students is often seen as a coping mechanism for some students who are prone to extreme stress, depression, or anxiety. Multiple forms of stress become the leading factors that push students toward substance use. This study tests the effects of college stressors, depression, and anxiety on substance use among college students. The results are based on the data that were collected using a 101-item questionnaire administered to 302 college students at a public university in the Midwest U.S.A. Using Logistic Regression as the primary data analysis technique, the findings of this study show that social stressors and time management stressors are the most significant predictors of substance use among college students. On the other hand, students scored very low on both depression and anxiety scales. These findings suggest that, in this context, depression and anxiety are not strong predictors of substance use among college students.